PEMBERDAYAAN MASYARAKAT DI DESA BHAKTI IDAMAN KECAMATAN MENDAHARA KABUPATEN TANJUNG JABUNG TIMUR MELALUI PENDIRIAN BANK SAMPAH - Aisyah Aisyah; Sri Dewi (PHI: Jurnal Pendidikan Matematika, 2017)
The establishment of this Garbage Bank aims to be an educational financing strategy that is accompanied by community awareness of environmental hygiene. In an effort to get direct benefit from garbage, in the form of waste saving which is directed to finance the education of children of Bhakti Idaman village community. So that the immediate benefits felt by the community are not only clean, healthy and comfortable environment but also human resource development which is expected to be able to manage community life well in the future. The method that will be done is 1) To socialize the establishment of BSI through education of household based waste management system, by giving rewards or benefit. 2) Establish a BSI management consisting of environmental activists, environmental cadres and communities and supporting parties (village government etc. 3) Training BSI managers through administrative management education and structural management patterns as well as designing BSI activities and sustainability. 4) Preparing the completeness of BSI which is consumables and administrative completeness. 5) Search for garbage buyers. 6) Promote the establishment of BSI through schools that have established cooperation, village government, activities undertaken by BSI and other ways that are considered strategic. 7) Performing waste saving services that benefitnya given in the form of savings education and financial savings family. 8) Monitoring and evaluation is conducted every two months to monitor progress and evaluate BSI performance. The result of this activity is the establishment of a household-based BSI with the benefits of education savings and family financial savings.Keywords: BSI, Education Savings.